Electro- and thermophysical properties of water-based nanofluids containing copper ferrite nanoparticles coated with silica: Experimental data, modeling through enhanced ANN and curve fitting. (December 2018) - Alrashed, Abdullah A.A.A.; Karimipour, Arash; Bagherzadeh, Seyed Amin; Safaei, Mohammad Reza; Afrand, Masoud
Graphical abstract: XRD pattern for dry CuFe2 O4 /SiO2 nanoparticles. Highlights: CuFe2 O4 /SiO2 nanoparticles were synthesized and then, dispersed in distilled water. Effect of T and φ on nanofluids' µ and σ was evaluated experimentally. Sensitivity analysis, enhanced ANN and curve fitting were employed to predict µ and σ values. More temperature corresponds to mildly increase of electrical conductivity. Abstract: A new homogeneous nanofluid of copper ferrite nanoparticles coated by silica dispersed in distilled water as the base fluid is prepared in a way to avoid settling and agglomeration. The values of dynamic viscosity and electrical conductivity at various temperatures and nanoparticles concentrations are experimentally measured. In addition, two empirical correlations are provided for them by the curve fitting approach. Moreover, the sensitivity analysis beside an enhanced artificial neural network is presented to accomplish the obtained results. The margin of deviations and experimental results versus those of correlations, imply the suitable accuracy of the proposed correlation. It is shown that more temperature corresponds to less dynamic viscosity; it also mildly increases the electrical conductivity. However, the effect of nanoparticle concentrations is more significant.